"Maintaining Order over Chaos": A study of the ba and baw concepts in the Predynastic Period, Early Dynastic Period, and Old Kingdom - van Sittert, Bianca (AUC Knowledge Fountain, 2020)
Among the corpus of ancient Egyptian religious terminology, bA and bAw stand out as two of the oldest, most wide-spread, and enduringly used terms. From the 1st Dynasty until the very end of ancient Egyptian history, these terms were utilized in a wide variety of contexts, including divine, royal, and non-royal names, titles, and epithets, didactic literature, and mortuary, administrative, temple, and royal propagandistic texts. However, despite their prominence and significance in the ancient Egyptian textual record, the function and meaning of these terms are still imperfectly understood, as evidenced by the multiple and varying translations within the Egyptological literature. A major issue which has contributed to this state of research is the fact that the origins, early function, and original meaning of bA and bAw have not been comprehensively investigated. This thesis is a study of the earliest material pertaining to the terms bA and bAw from the Late Predynastic Period to the end of the Old Kingdom. The material analyzed includes Late Predynastic art in which the stork (Saddlebill stork, signs G29 & G30) later used as a hieroglyph for bA and bAw appears, as well as a large corpus of Early Dynastic and Old Kingdom texts (1st-6th Dynasty names, titles, and epithets; the Pyramid Texts, and two 6th Dynasty non-royal texts). Through a chronological study of this iconography and of these texts, it was demonstrated that (a) the original ideas and principles encompassed within the terms bA and bAw are apparent in Late Predynastic Saddlebill stork images, (b) that the terms bA and bAw originally functioned to express divine and royal ideology and that their use in the earliest royal mortuary texts was an extension of this function, and (c) that these terms essentially signified, reinforced, and perpetuated the fundamental ancient Egyptian doctrine of "Order over Chaos" or mAat vs. isft.